(untitled) (Medical Forum Monthly, 2022)
Objective: To find out the incidence of oral lichen planus in patients having diabetes mellitus. Study Design: Cross-sectional Study. Place and Duration of Study: This study was conducted at the Oral Medicine out –patient clinic in Islam Dental College, Sialkot over a span of eleven months from October 2020 to September 2021. Materials and Methods: 500 diabetic patients with an age range of 45-65 years were examined clinically for the features of oral lichen planus using mouth mirror and explorer in the dental clinical settings. Patients having no pain with white striations on mucosa were considered for reticular lichen planus while patients having burning and pain were considered for ulcerative lichen planus. Results: Among 500 diabetic patients, 18 patients ( 3.6% ) were found with Oral lichen planus and these patients were having type II diabetes. Conclusion: It was found that the prevelance of oral lichen planus in Diabetic patients was only 3.6% percent which is significant. But alone elevated sugar levels can’t be the entire reason as other factors likes stress, anxiety etc to which these diabetic patients might have been exposed can also play role in causing this oral condition.